A novel automated simulator of pediatric systemic circulation: Design and applications. (September 2021) - Torres, Daniel S.; Mazzetto, Marcelo; Cestari, Idágene A.
Highlights: Heart transplantation is frequently the final treatment option in advanced heart failure. The use of ventricular assist devices as a bridge to heart transplantation improves survival. There is a great need of developing pediatric specific ventricular assist devices. Simulators of the circulation can assess the performance of ventricular assist devices. Automation makes simulators practical tools for research and learning. Abstract: The technology of ventricular assist devices has shown unprecedented evolution over the last decade. Despite of it, there is still a great need of developing pediatric specific devices, thus highlighting the demand for flexible simulators, capable of emulating mechanical circulatory assistance in the setting of pediatric heart failure. The aim of this work was to design and build an automated simulator of the pediatric circulation. The simulator comprises a hydraulic circulation mock loop and an electronic system with its computational algorithms and its graphical user interface. The simulator includes left ventricle assist devices capable of generating pulsatile or continuous-flow. To demonstrate the applicability of the automated system developed, normal and heart failure conditions of pediatric patients were simulated and the contribution of left ventricular assist devices in restoring normal hemodynamics were quantified. Restoration of aortic flow was obtained with the use of continuous or pulsatile devices in heart failure simulated conditions. The system is user friendly and intuitive, allowing fast and reproducible adjustments of parameters, such as vascular resistance and compliance, and left ventricle preload, providing environments suitable for in vitro evaluation of pediatric left ventricle assist devices.